e-Performance Appraisal Form (e-PAF) / Alisa Syafawati Mohd Azri … [et al.] - Mohd Azri, Alisa Syafawati; Mohd Subhe, Nur Syafiqah; Ruzaimi, Nurul Athirah; Zakaria, Nurul Fatihah; Mohd Zin, Zahidah Nazura; Krishnan, Ramesh (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
In the industrial sector, performance appraisal is vital to evaluate an employee's performance based on how they have performed in the recent past and for superiors to provide feedback on the employee's performance in a company. According to Mayank (2020), performance evaluation aims to rate employees based on their performance over the past year. It plays a significant part in determining employee compensation, whether they are eligible for a promotion, and whether they should continue working for the firm. Yet, the more we live in a globalized world, the more proficiently we must use technology. Consequently, an increasing number of firms, both large and small, have replaced the manual evaluation form with an e appraisal form, which greatly simplifies the work of everyone, particularly the person responsible for conducting the evaluation and the employees themselves. As such our focus here is to develop a e-appraisal form to be used in a work organization. Accordingly, this study aims to present an e-appraisal innovation idea, its aims, and methods for conducting performance evaluations. This product is designed for large companies as well as for small and medium sized companies which still using manual performance appraisal forms. This e appraisal form is expected to help HR professionals, managers and supervisors to understand the idea and the most effective way to implement it.